2013
DOI: 10.1111/anu.12053
|View full text |Cite
|
Sign up to set email alerts
|

Fishmeal can be totally replaced by plant protein blend at two protein levels in diets of juvenile Siberian sturgeon,Acipenser baeriiBrandt

Abstract: An 8‐week growth trial was conducted to evaluate the effects of a plant protein blend (PPB, comprised of soybean meal and wheat gluten meal) as fishmeal (FM) substitute on growth, nitrogen (N) and phosphorus (P) balance in Siberian sturgeon, Acipenser baerii Brandt. Two control diets were formulated to contain two protein levels (400 and 360 g kg−1). At each protein level, FM was totally replaced by PPB with supplement of crystalline essential amino acids and mono‐calcium phosphate. Growth performance was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 52 publications
4
19
0
Order By: Relevance
“…In other word, hybrid sturgeon can tolerate the low fishmeal feed in a specific range. This result coincided with the previous research of Yun et al (), who found that the growth performance of Siberian sturgeon was not affected by dietary protein sources and protein levels. Moreover, Xue et al () also reported that total fishmeal protein replaced by animal protein blend and supplemented with EAA did not show significant negative effect on growth of Siberian sturgeon.…”
Section: Discussionsupporting
confidence: 93%
“…In other word, hybrid sturgeon can tolerate the low fishmeal feed in a specific range. This result coincided with the previous research of Yun et al (), who found that the growth performance of Siberian sturgeon was not affected by dietary protein sources and protein levels. Moreover, Xue et al () also reported that total fishmeal protein replaced by animal protein blend and supplemented with EAA did not show significant negative effect on growth of Siberian sturgeon.…”
Section: Discussionsupporting
confidence: 93%
“…The RIs of FM, PPBM and WGM were nearly one, suggesting that the water-soluble extracts from these protein sources have much better palatability to turbot. Yun et al (2014) pointed out that FM is a high quality protein source for aquaculture. It was characterized by high protein content, favorable amino acid profile, no anti-nutritional factor, and reasonable palatability.…”
Section: Discussionmentioning
confidence: 99%
“…Yun et al. () found that there was no difference in SGR or FE in Siberian sturgeon, A. baerii fed diets with all the FM replaced with the plant protein blend (SBM:wheat gluten meal = 6:4) with or without lysine, methionine and threonine supplementation. To reduce the negative effect of high level substitution on fish growth, many authors have used successfully simple or complex mixtures of plant ingredients to replace FM in aquaculture feeds (Borgeson, Racz, Wilkie, White, & Drew, ; Hung, ; Kaushik, Covès, Dutto, & Blanc, ); as this might reduce the exposure to individual ANFs.…”
Section: Introductionmentioning
confidence: 99%